2015
DOI: 10.3109/09638288.2015.1019648
|View full text |Cite
|
Sign up to set email alerts
|

What is it like to walk with the help of a robot? Children’s perspectives on robotic gait training technology

Abstract: Rehabilitation professionals, researchers and parents are encouraged to reflect on why and how one might engage children in gait-related rehabilitation in ways that appeal to children's desires and expectations. This may shape how interventions are presented to children and how goals and outcomes are framed. Implications for Rehabilitation Children in this study did not consistently feel excited about, have a wish to use, or have a sustained interest in the use of a robotic technology, and at times experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…This could be ascribed to the lack of specific instruments able to describe clinical aspects related to the various RAGT devices actually available in rehabilitation. Only few examples without structured questionnaires exist regarding stroke [ 8 ], SCI [ 9 ] and cerebral palsy [ 10 ]. For this reason, in the present pilot study, we evaluated the psychosocial impact of RAGT (Lokomat ® ) as delivered in a real-world hospital setting by means of the PIADS questionnaire [ 13 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be ascribed to the lack of specific instruments able to describe clinical aspects related to the various RAGT devices actually available in rehabilitation. Only few examples without structured questionnaires exist regarding stroke [ 8 ], SCI [ 9 ] and cerebral palsy [ 10 ]. For this reason, in the present pilot study, we evaluated the psychosocial impact of RAGT (Lokomat ® ) as delivered in a real-world hospital setting by means of the PIADS questionnaire [ 13 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RAGT seems not only to improve objective measurements of performance but also the perception of well-being in stroke patients [ 8 ], in SCI patients [ 9 ] and in children with cerebral palsy [ 10 ]. Although the importance of this aspect has been stated by World Health Organization (WHO) in the International Classification of Functioning, Disability and Health (ICF) as one of the three major components of disability and health [ 11 ], data on the patient-robot relationship through a psychosocial perspective are scant and, to the best of our knowledge, limited to the above mentioned reports.…”
Section: Introductionmentioning
confidence: 99%
“…The ''critical'' piece of our theoretical framework refers to challenging the value-laden assumptions underlying how we understand and talk about technology and rehabilitation practice. Technology's effects can range from substantial and ''game-changing'' to subtle and nuanced yet still important to society and individuals (Lehoux et al, 2014;Phelan et al, 2015). For example, the theory of disruptive innovations argues that particular leaps in technology can have substantial effects on society by disrupting entire markets and changing the status quo (Christensen et al, 2000;Hwang and Christensen, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Body function measures, for example, may not be of high importance for young children with disabilities, as they refer to their usual walking pattern as "normal" and do not necessarily aim to walk in so-called typical gait patterns. 50 Our systematic review on gait-related activity measures showed us that many tools that are used in clinical routine and research have no or only very limited evidence on their psychometric properties. Furthermore, also the relevance of these measures for the children or their families is often questionable.…”
Section: Chaptermentioning
confidence: 99%
“…Similarly, moderate positive evidence was found for intrarater reliability of the Functional Walking Test 49 and the MobQues28 and MobQues47 32 as well as for interrater reliability of the MobQues28/47 in children with CP. 32 Limited positive evidence for reliability in children with CP was available for the following instruments: the 10X5-Meter Sprint Test, 43 the 10-Meter Fast Walk Test, 28 the ABILOCO-Kids, 45 cadence measured with the GAITRite, 31,46 gait speed measured with a stopwatch, 50 and the Quality Analog Scale. 55 Also, limited positive evidence for reliability was available for the Community Balance and Mobility Scale in children with acquired brain injury 47 and the walking scale of the Functional Assessment Questionnaire in children with mixed neuromuscular diagnoses.…”
Section: Reliabilitymentioning
confidence: 99%